Cultivating the Curiosity Amplifier: An Investigation into the use of the iPad as a tool for learning in the Irish Primary Music Curriculum - Brennan, Simon (Trinity College (Dublin, Ireland). School of Education, 2021)
The iPad has become ubiquitous in Irish education with its efficacy in supporting school inclusion, as well as learning in core subjects well documented. The iPad has also proven to be popular with musicians availing of the many music applications accessible to its users. Yet, in Irish primary music education, there is a dearth of research pertaining to the implementation of the iPad as a medium for musical learning. Operating in a teacher role, the researcher investigates how the iPad can be used in the learning of the three strands of the Irish primary music curriculum, namely, listening and responding, performing and composing, from a student perspective. The study also examines the iPad’s efficacy as a tool for musical learning in these strands. The study group comprises twenty-nine participants from a fourth/fifth class located in a rural Irish setting. Employing a triangulated mixed methods approach underpinned by a pragmatist philosophical position, quantitative data were gathered in the form of questionnaires that bookend the study, while qualitative data were gathered through the use of six online reflective journals. Audio recordings of compositions and performances were made by participants as secondary data. Findings in the study suggest that the iPad can be used successfully by students as an intimate listening device that promotes focused listening when appraising musical works, as an instrument for learning and performing tunes and as a device for exploring sounds, composing and recording.
Keywords: Music in Education; Education